Implementasi Pemasaran Digital Pada Breadlife Melalui Media Video - Arienda Gitty Ramadani; Dewi Khornida Marheni; Fanesha Nissy Kusweanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
Digital Marketing is the main key for business in these days to be able to thrive. Breadlife Batam is a store specialized in selling and making bread and pastry in an Japanese Artisan Bakery style under PT Kunci Mas Batam. All this time, there are some Batam residents which do not recognize Breadlife as a good national franchise, have not tried the products and also feel sceptic towards the brand quality, considering the price is expensive enough if compared to other local bread brands.Purpose - This PkM activity is expected to be able to help Breadlife store to promote its product to the society with video media.Research Method - The data collection method used is observation and interview. Findings - As a result, there are many good responds from the society, hence Breadlife brand will be increasingly known by the Batam societies. Implication - The contribution of the research findings for Breadlife’s owner are many good responds from the society, hence Breadlife brand will be increasingly known by the Batam societies. The contribution of the research findings for the next researcher are can be used as a reference source for further research to support research related to digital marketing.